Numerical analysis of embedded reinforced soil foundation on two-layer soil system / Ng Kok Shien and Siti Fatimah Sadikon - Ng, Kok Shien; Sadikon, Siti Fatimah (Research Management Institute (RMI), 2010)
The behaviour of strip footings resting on subsoil consisting of a reinforced-granular fill layer overlying a low bearing capacity soil was studied. Model setup was divided into two: surface footing and embedded footing. A series of finite element (FE) analysis were performed on a prototype model of both reinforced and unreinforced foundations using FE commercial software PLAXIS. Updated mesh analysis based on Updated Lagrangian formulation was adopted in this study. The purpose of this study is to determine the effect of geosynthethics reinforcement on the ultimate bearing capacity and settlement characteristics of the strip footing resting on a granular fill – soft soil system. Particular emphasis is paid on the fill depth, embedment depth, fill and soft soil strength, reinforcement stiffness and length, and number of reinforcement layer. Besides, investigations on effects of laying geosynthethics at the interface or into the layer of fill were studied. The method of analysis was verified by comparison with analytical solution and previous study. Based on the result, the reinforcing effect of two layer soil system is quantitatively evaluated.